Zadanie 4. ( 0p. - 20p.) Uprość wyrażenia:

2x - 7xy + 9y - 5,5 + 2,4 x + 3xy -19 y + 12 =

- ( - a + 3b - 13 ) - ( 7a + 2b - 15 ) - 5a =

2x(x - 7y + 5 ) - 4(x2 - xy +7 ) - 6x22 =

(2x - 5y) (-3x + 2y) - ( x - y)(x + y)=

x(3x - 7y -1) - (2x - 5y)2 + 4x2=



Odpowiedź :

Odpowiedź:

4,4x-4xy-10y+6.5

+a-3b+13-7a-2b+15-5a=-11a-5b+28

2x(x - 7y + 5 ) - 4(x2 - xy +7 ) - 6x22 =2x2-14xy+10x-4x2+4xy-28-  ?=-2x2-10xy+10x-28-....

-6x2+4y+15xy-10y2-(x2+xy-xy-y2)=-6x2+4y+15xy-10y2-x2+y2=.....

3x2-7xy-x-4x-10y+4x2=....

Szczegółowe wyjaśnienie: